Novel presenilin-1 mutation with widespread cortical amyloid deposition but limited cerebral amyloid angiopathy. Issue 2 (1st February 2000) - Yasuda, Minoru; Maeda, Sakan; Kawamata, Toshio; Tamaoka, Akira; Yamamoto, Yasuji; Kuroda, Shigetoshi; Maeda, Kiyoshi; Tanaka, Chikako
Abstract : OBJECTIVE: To clarify the phenotypic heterogeneity in deposition of amyloid beta (Aβ) in the parenchyma and in cerebral vessels of the brains of the patients having presenilin-1 (PS1) mutations. Mutations in PS1 induce increased production of Aβ42(43), resulting in an enhanced overall deposition of Aβ protein within the cerebral cortex. METHODS: Sequence analysis of the PS1 gene of DNA from patients with early onset Alzheimer's disease, and immunostaining of brain tissues by end specific monoclonal antibodies against Aβ. RESULTS: Sequence analysis disclosed a novel mutation (N405S) in the PS1 gene in a Japanese patient with early-onset Alzheimer's disease. Postmortem examination of one patient with N405S showed limited cerebral amyloid angiopathy, whereas postmortem examination of another Japanese patient with Alzheimer's disease with the E184D mutation disclosed severe cerebral amyloid angiopathy. The brains of both patients showed widespread neuritic plaques, neurofibrillary tangles, and neuronal loss. Immunostaining showed that Aβ42 was predominant over Aβ40 in neuritic plaques in both patients, whereas Aβ40 was found to be predominant over Aβ42 in cerebral amyloid angiopathy in the patient with E184D. However, most cortical vessels of the patient with N405S were not reactive with either of the antibodies. CONCLUSION: The N405S mutation of PS1 is a major determinant of cortical Aβ deposition but not cerebral amyloid angiopathy in Alzheimer's disease.